2020
DOI: 10.1111/jpn.13365
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate and presence of protozoa increase nitrate and nitrite reduction in the rumen of sheep

Abstract: Nitrate ( NO3- ) supplementation is an effective methane (CH4) mitigation strategy for ruminants but may produce nitrite ( NO2- ) toxicity. It has been reported that rumen protozoa have greater ability for NO3- and NO2- reduction than bacteria. It was hypothesised that the absence of ruminal protozoa in sheep may lead to higher NO2- accumulation in the rumen and a higher blood methaemoglobin (MetHb) concentration. An in vivo experiment was conducted with defaunated (DEF) and faunated (FAU) shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In the rumen, metabolic interactions between ciliate protozoa and nitrate/nitrite reducing bacteria have been proposed. When co-cultured with bacteria, rumen protozoa were reported to accelerate nitrate reduction 11 , and the protozoal fraction, which likely included both protozoa associated prokaryotes showed a greater ability to reduce nitrate without accumulation of nitrite. The possibility that, combined nitrate reduction to nitrite by protozoa, for which genomic evidence exists, with production of hydrogen may lead to the enrichment of nitrite reducing bacteria 52,53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rumen, metabolic interactions between ciliate protozoa and nitrate/nitrite reducing bacteria have been proposed. When co-cultured with bacteria, rumen protozoa were reported to accelerate nitrate reduction 11 , and the protozoal fraction, which likely included both protozoa associated prokaryotes showed a greater ability to reduce nitrate without accumulation of nitrite. The possibility that, combined nitrate reduction to nitrite by protozoa, for which genomic evidence exists, with production of hydrogen may lead to the enrichment of nitrite reducing bacteria 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their still elusive ecological dynamics, ciliate protozoa have also been suggested to have many metabolic and physiological functions in the rumen, most of which not yet elucidated 10 . Some of these functions are further suggested to be a direct consequence of their interactions with the prokaryotic community 11,12 . The most studied functional interaction is their role in enhancing methane production via interspecies hydrogen transfer to methanogenic archaea 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Ciliated protozoa populations increased significantly as a result of feeding the NIT diet, which is in line with the results obtained in goats ( Zhang et al., 2019 ) and in vitro studies ( Lin et al., 2011 ). Furthermore, in a recent in vivo experiment with defaunated and faunated sheep supplemented with 1.8% of nitrate (on a DM basis), it was reported that nitrate metabolizes more rapidly in the presence of ruminal protozoa, and defaunated sheep may have an increased risk of poisoning due to nitrite accumulation in the rumen ( Villar et al., 2020 ). In contrast, Iwamoto et al.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results are mixed, and while ruminal ciliate contributions to nitrate reduction have been noted during methane mitigation, an understanding of the mechanisms involved remains incomplete. Further, an enhanced metabolic reduction in nitrate and nitrite has been observed in faunated conditions in both in vitro and in vivo studies [ 62 ], with ciliates and associated bacteria potentially contributing to nitrite reduction [ 63 ]. This interaction highlights the role of ruminal ciliates in ensuring the safe application of nitrate for methane mitigation.…”
Section: Introductionmentioning
confidence: 99%